2017
DOI: 10.14311/nnw.2017.27.002
|View full text |Cite
|
Sign up to set email alerts
|

<em>FbMapping</em>: AN AUTOMATED SYSTEM FOR MONITORING FACEBOOK DATA

Abstract: A method for identification of mechanical parameters of an asynchronous motor is presented in this paper. The identification method is based on the use of our knowledge of the system. This paper clarifies the method by using the example identifying of mechanical parameters of the three-phase squirrel-cage asynchronous motor.A model of mechanical subsystem of the motor is presented as well as results of simulation. The special neural network is used as an identification model and its adaptation is based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The correlation between the original image and the adversarial sample was assessed using 𝐿 𝑝 norms. The generally used p-norm metrics for assessing perturbation magnitude are 𝐿 0 , 𝐿 2 , and 𝑑(𝑥, 𝑥′) is a distance constraint that should be less than some value ε as represented in (4).…”
Section: E Perturbation Measurement Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between the original image and the adversarial sample was assessed using 𝐿 𝑝 norms. The generally used p-norm metrics for assessing perturbation magnitude are 𝐿 0 , 𝐿 2 , and 𝑑(𝑥, 𝑥′) is a distance constraint that should be less than some value ε as represented in (4).…”
Section: E Perturbation Measurement Metricsmentioning
confidence: 99%
“…The use of deep learning changed human life in many fields. Computer vision is the field of deep learning that is increasingly used in many applications, from disease prediction [1][2][3] to automated surveillance systems [4]. The advent of many deep learning technologies has given rise to protecting computing systems from digital attacks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey has revealed that ANN could be efficiently used for weather prediction tasks [26]. In spite of immense success of ANN based models in predicting weather parameters, it suffers from a significant problem regarding the training algorithms.…”
Section: Introductionmentioning
confidence: 99%